PENGARUH KESESUAIAN KOMPENSASI DAN KULTUR ORGANISASI TERHADAP PERSEPSI PEGAWAI ATAS FRAUD DI INSTANSI PEMERINTAHAN KOTA MANADO - Jecklein, .; Kalangi, Lintje; Walandouw, Stanley Kho (JURNAL RISET AKUNTANSI GOING CONCERN, 2019)
This study aimed to explore the employee perceptions of fraud in government agencies and the factors that influence the occurrence of fraud . The variables used in this study are the compliance of compensation and culture of organization as independent variables and fraud in government agencies as the dependent variable. Samples used in this research as many as 60 respondents from government agencies in Manado, especially in the Regional Financial and Asset Management Agency and the Office of Public Works and Spatial Planning of the City of Manado. Sampling technique uses purposive sampling and data collection used questionnaires. The analysis in this study used multiple linear regression analysis with the help of SPSS version 23 application. The results showed that, there is no influence of the appropriateness of compensation by fraud in Manado City government agencies, and there is a significant negative effect on fraud in Manado City government agencies.Keywords: compatibility compensation, organizational culture, fraud, government agencies